2020
DOI: 10.1111/1755-0998.13148
|View full text |Cite
|
Sign up to set email alerts
|

Testing multiple substrates for terrestrial biodiversity monitoring using environmental DNA metabarcoding

Abstract: Biological surveys based on visual identification of the biota are challenging, expensive and time consuming, yet crucial for effective biomonitoring. DNA metabarcoding is a rapidly developing technology that can also facilitate biological surveys. This method involves the use of next generation sequencing technology to determine the community composition of a sample. However, it is uncertain as to what biological substrate should be the primary focus of metabarcoding surveys. This study aims to test multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 93 publications
6
47
0
Order By: Relevance
“…Genetic data facilitate in‐depth analyses of different demographic scenarios that shape genetic patterns of diversity and can clarify species vulnerability and population status to extinction risk under future climate change (Harrisson et al, 2014). In the past decade, the field of molecular ecology has witnessed the development of effective metabarcoding‐based tools for ecological assessment from various sample types in a variety of different ecosystems (van der Heyde et al, 2020; Mariani et al, 2019; Wangensteen et al, 2018). However, the intraspecific diversity of species from the enormous availability of metabarcoding biodiversity data sets remains hidden, and until recently, few studies have attempted to harness this concealed genetic component from environmental and community DNA (Elbrecht, Vamos, et al, 2018; Parsons et al, 2018; Sigsgaard et al, 2016; Tsuji et al, 2020; Turon et al, 2020; Zizka et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic data facilitate in‐depth analyses of different demographic scenarios that shape genetic patterns of diversity and can clarify species vulnerability and population status to extinction risk under future climate change (Harrisson et al, 2014). In the past decade, the field of molecular ecology has witnessed the development of effective metabarcoding‐based tools for ecological assessment from various sample types in a variety of different ecosystems (van der Heyde et al, 2020; Mariani et al, 2019; Wangensteen et al, 2018). However, the intraspecific diversity of species from the enormous availability of metabarcoding biodiversity data sets remains hidden, and until recently, few studies have attempted to harness this concealed genetic component from environmental and community DNA (Elbrecht, Vamos, et al, 2018; Parsons et al, 2018; Sigsgaard et al, 2016; Tsuji et al, 2020; Turon et al, 2020; Zizka et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we analyse eDNA from cattle dung using eDNA metabarcoding, but with a focus on the dung-associated invertebrate fauna rather than the diet of the herbivore. Van der Heyde et al (2020) recently found beetle DNA in scat samples from herbivores, supporting the idea that faecal samples may contain eDNA from invertebrates that have come in contact with the substrate after defecation. We hypothesize that dung-associated invertebrates leave DNA traces in the dung, and investigate: (i) to what extent this eDNA can be obtained, (ii) whether it reflects the taxonomic and functional diversity…”
Section: Introductionmentioning
confidence: 77%
“…This pipeline consists of trimming, filtering, a learning error model from the sequence data, dereplication, correcting errors based on the error model, merging paired-end reads, removing chimera, and a generating amplicon sequence variants (ASV) table. The ASV can be analyzed in a similar way to the traditional operational taxonomic unit (van der Heyde et al, 2020). We processed the ASV table in a specific manner to reduce false positives of target species: for some Illumina sequencers (e.g., Hiseq X and iSeq 100) with patterned flow cells and ExAmp chemistry, free-floating indexing primers that remain in the library can cause a read misassignment called index hopping (Costello et al, 2018), which can cause false positives of the target taxa in DNA metabarcoding.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of detection methods for hard-to-find taxa is needed to accurately assess local biodiversity. Recently, the environmental DNA (eDNA) survey was developed as an efficient and sensitive approach to determine the distribution of rare aquatic species (Thomsen and Willerslev, 2015). Several studies applied the eDNA survey to aquatic plants and successfully detected the target species among collected samples in aquariums, rivers, and ponds (Scriver et al, 2015;Fujiwara et al, 2016;Matsuhashi et al, 2016;Gantz et al, 2018;Kuzmina et al, 2018;Anglès d'Auriac et al, 2019;Chase et al, 2020;Coghlan et al, 2020;Doi et al, 2020;Kuehne et al, 2020;Miyazono et al, 2020).…”
Section: Introductionmentioning
confidence: 99%